Hedges and Boosters in the Discussion Sections of Tourism and Pharmacology Research Articles - Nur Zafirah Razali (Penerbit UMP, 2022)
The Discussion section of research articles (RAs) is a section where authors place their ideas and interpret their research findings by strengthening and making sense of the findings to benefit the communities in their fields or others. Academic writing is incorporated with mitigating devices and expressions that convey the attitudes of authors and communication abilities, such as the expressions of doubt (hedges) and certainty (boosters), which are important to the rhetorical nature of academic writing. Thus, given the strong roles of these mitigating devices in expressing certainty and uncertainty in the Discussion section of RAs, improper use of hedges and boosters will make it difficult for authors to state what they imply, and this may lead to a misunderstanding of what the authors attempt to convey or interpret in their writing. Through the taxonomies of hedges and boosters, this study investigates the use of hedges and boosters as well as identifies the similarities and differences in the use of hedges and boosters between 20 Tourism RA discussions and 20 Pharmacology RA discussions using a mixed method. Data were also supplemented using interviews with Tourism and Pharmacology specialist informants. Overall, the findings revealed that academic authors from both Tourism and Pharmacology fields used more hedges than boosters to avoid any overstatement of their research results. This study will assist authors and students in the use of hedges and boosters, particularly in academic writing.